Development Process of Brand Identity and Community Participatory Packaging of Ban Sao Luang Weaving Group Community Enterprise, Bo Suak Sub-district, Mueang District, Nan Province. - Panpaisarn , Usuma; Morathob , Nichapa (Sripatum Review of Humanities and Social Sciences, 2024)
Research on The process of developing brand identity and community packaging with participation of the Ban Sao Luang Weaving Group community enterprise, Bo Suak Subdistrict, Mueang District, Nan Province, has two important objectives: 1) to study community identity from social and cultural capital. Participate in the community enterprise group, Ban Sao Luang Community Weaving Group, and 2) To develop brand design and identity packaging through participatory processes participatory identity of the Ban Sao Luang community weaving enterprise group It is participatory action research. (Participatory Action Research: PAR) collects data through hands-on activities. group chat and brainstorming meeting From the committee and community enterprise members Including 45 representatives of local government agencies, analyzing content data and using T-Test statistics. From the study results it was found that The community enterprise of the Ban Sao Luang Community Weaving Group has a context and identity of Social and cultural capital through the “Bor Suak pattern” (a pattern resembling an owl in a lotus petal frame with a cut tip resembling an epaulette) that was modeled after the pattern on the mouth of an ancient jar that was endemic to Nan in the past. Created as the brand "Int Kham Saeng", meaning the prosperity of ancient hand-woven fabric. which inspired the 800 year old jar into the fabric Emphasis on using the natural colors of the Nonsi tree. As for the process of designing branding and community identity packaging, it was found that Collaborative decision-making takes place in selecting patterns and packaging styles that convey the distinctiveness of the group. As well as being able to reflect the weaving lifestyle in the Ban Sao Luang community. Three types of prototypes were obtained for commercial use: 1) brand tags, 2) brand stickers, and 3) packaging. In terms of cost, it was found that There is no impact on the original cost when compared. And the satisfaction evaluation results comparing the original brand and product with the new brand and product were significantly different at the 0.5 level (t=3.64). There is a low level of satisfaction with the old brand and product format (x̅=2.55) and a high level of satisfaction with the new brand and product format (x̅=4.29).